The Very Hungry Caterpillar's Very First Encyclopedia - Carle, Eric; Evatt, Joy (New York, New York, 2022)
An early reader's encyclopedia featuring Eric Carle's Very hungry caterpillar.
Our world -- Body and health -- Earth -- Animals and nature -- History -- Science, math and technology -- Space.
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries; Encyclopedias